HIV advocacy: knowledge translation and implementation at three diverse sites in sub-Saharan Africa. Issue 26 (18th December 2022) - Myezwa, Hellen; Nixon, Stephanie; Potterton, Joanne; Ajidahun, Adedayo Tunde; Cameron, Cathy; Konje, Moses; Omoroh, Florence; Chiluba, Brian Chanda; Chisoso, Theresa; Solomon, Patricia
Abstract: Purpose: To explore how the gap in knowledge translation around HIV and rehabilitation could be addressed using advocacy. This article describes and reflects on lessons learned from incorporating content on HIV and advocacy into the curricula at three diverse physiotherapy (PT) programs in sub-Saharan Africa. Methods: A realistic evaluation approach was followed. Three study sites were purposively chosen to reflect diverse settings with respect to pedagogical approach, university or college, degree or diploma programs, use of technology, and regional prevalence of HIV. A multi-faceted intervention was implemented that included three activities: (i) to develop three core components of a novel knowledge translation intervention designed to improve knowledge, attitudes, and self-efficacy in HIV and rehabilitation advocacy among PT students; (ii) to tailor and implement the knowledge translation intervention by local faculty according to the context and needs of their program and to implement this with a cohort of PT students at each of the three study sites; and (iii) to evaluate the adaptation and implementation of the intervention at each site. Results: Differences exist between the three-country programmes, specifically in the length of time the degree takes, the extent of HIV inclusion in the curriculum and years of the study included in the project. Conclusions: This research adds to the call to shift the focus of HIV care from just test-and-treat, or on just keeping people alive, towards a broader approach that centres the whole person, that focuses not only on surviving but on thriving, and which commits to the goal of optimising functioning and living full, whole lives with HIV. Advocacy across the continuum of care plays a pivotal role in translating research findings into practice. Implications for rehabilitation: Results are relevant for policymakers in government and at senior levels within universities whose mandates include informing, reviewing, and driving educational programs and curricula. The result from this project illuminates the role for rehabilitation and allows for incorporating HIV into curriculum and practice for physiotherapists and other related stakeholders so that they can advocate for and with patients.